Analysis and Development of a School Platform with a User Experience Approach at Samirejo 3 Elementary School - Jannah, Zuliana Nurul; Riadi, Aditya Akbar; Meimaharani, Rizkysari (INOVTEK Polbeng - Seri Informatika, 2026)
The digitization of educational services has become an important need for schools to improve the effectiveness of data management and information delivery. Samirejo 3 Elementary School still applies manual processes in attendance recording, information management, and communication with parents, resulting in frequent delays and inaccuracies in data. This study aims to analyze and develop a web-based school platform using a user experience (UX) approach to make the system easier to use and better suited to user needs. The research methods include observation, interviews, and literature study, while system development uses the Waterfall model. System evaluation is conducted using User Acceptance Testing (UAT) and the System Usability Scale (SUS). UAT involved 10 respondents consisting of admins, teachers/class guardians, and parents, with an average result of 95.6%, indicating that the system was very well accepted. UX testing using the SUS method involved the same respondents and obtained an average score of 79, which falls into the "Good" category, indicating that the system is easy to understand, efficient, and comfortable to use. The research results show that this platform can enhance data management efficiency, accelerate information dissemination, and provide a more optimal user experience. Thus, the developed platform supports the school's digital transformation and improves the quality of information services at Samirejo 3 Elementary School.